Sponge density increases with depth throughout the Caribbean. Issue 12 (10th December 2018) - Lesser, Michael P.; Slattery, Marc
Abstract: Mesophotic coral reefs (MCEs) are ecologically unique components of coral reef ecosystems that occur at depths from 30 to 150 m where they support a high number of depth‐endemic species. One ecologically important taxonomic group that can, especially in the Caribbean basin, dominate these habitats are sponges where they occur throughout the shallow (<30 m) to mesophotic depth range. There are an increasing number of studies on MCEs generally, and sponges have become a focal area for many of these studies as they exhibit a number of ecological and functional traits that vary with increasing depth. Here, we use an analysis of both historical and contemporary data to test the recently described "sponges increase with depth" hypothesis. While this hypothesis has recently been rejected without benefit of any quantitative analysis, we show that the density or percent cover of sponges increases over the shallow to mesophotic depth range for multiple reef sites in the Caribbean, and also in the Pacific at selected sites. The proximate cause for this pattern appears to be the increasing availability of trophic resources, and the ability to differentially use those resources, with increasing depth. The increase in sponge density or percent cover with depth is potentially global in nature and results in diverse, and unique, sponge‐dominated communities at mesophotic depths.